PERAN PENGELOLAAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK PENINGKATAN KINERJA PERUSAHAAN (STUDI PADA PT. PRIBUMI CITRA MEGAH UTAMA) - Noorlaily Maulida; Periyadi Periyadi; Junaidi Junaidi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
The main objective in this study is to examine and analyze how the influence ofhuman resource development consisting of, recruitment , training, career development,compensation, promotion of position on company performance.This research was conducted with a qualitative method and using the SWOT analysisas a data analysis tool. The object of this research is PT. Pribumi Citra Megah Utama, whichruns its businesses such as hotels, shopping centers, housing, financing and mining in SouthKalimantan. Data that has been tested for its credibility with the triangulation technique ofdata sources, is then analyzed descriptively using the help of a data analysis modeldeveloped by Miles and Huberman. Miles and Huberman made a model of data analysisconsisting of three stages, namely: data reduction, data display, and conclusion drawing.Based on the results of research it can be found that the human resource managementstrategy plan to increase the productivity of employees of PT. Pribumi Citra Megah Utamais a business partner model strategy because this strategy has several advantages, namely theexistence of several strengths in the company that can be used to take advantage of severalopportunities and face several threats to the company. The methods carried out by PT.Pribumi Citra Megah Utama is to Reinforce and tighten company regulations which includeworking hours, employee responsibilities, work completion, accuracy of work completion.